STUDI KASUS SISWA YANG TIDAK BISA BERKONSENTRASI PADA PEMBELAJARAN DARING IPA DI KELAS VII SMP NEGERI 10 PONTIANAK - Elda, Serpiana; Wicaksono, Luhur; Fergina, Ana (Universitas Tanjungpura, 2023)
This study aims to find out about case studies of students who cannot concentrate on science online learning in class VII SMP Negeri 10 Pontianak. The case subjects in this study were two class VII students who could not concentrate in online learning. This study used a qualitative research approach with a descriptive research type in the form of a case study. Data collection techniques used were interviews, documentation and home visits. After conducting research on the two career subjects, it can be concluded that subject I concentrates more on learning, can adapt to online learning, is more enthusiastic about learning, and begins to fall asleep less in class. Whereas the subject of case II was able to solve learning difficulties, was more enthusiastic about learning, had new innovations in learning and did not fall asleep in class when online learning took place.